Аналіз параметрів ступенів свердловинних насосів для водопостачання - Каплун, Ігор Петрович; Оприско, Михайло Богданович (НТУ "ХПІ", 2015)
Проаналізовано основні параметри ступенів свердловинних насосів для фірм-виробників, що найбільш широко представлені на ринку України. Сформовано зведені графіки основних параметрів ступенів для умовних габаритів 8 та 10 дюймів. За зведеними графіками параметрів ступенів встановлено доцільні межі робочих діапазонів та подач для новостворюваного типорозмірного ряду свердловинних насосів на основі малогабаритних осьових ступенів. Запропоновано обмежити допустиме зниження коефіцієнту корисної дії ступені на границях діапазону на рівні 3 %.

The main aim of the article was to study the experience of development of borehole pumps and statistically analyze the parameters of their stages for major companies, presented on the market of Ukraine. The second goal was to consider forming a basis for the requirements to small-sized axial stages and their main parameters to create a competitive pump equipment. As a result of statistical analysis parameters of borehole pump’s stages the best parameters for dimensional size 8 "and 10" were determined, that might be used as a guide when the dimension-type series of borehole pumps based on the small axial stages creating. Based on the data summary charts parameters pre-selected three basic axial stages for the dimensional size 8 "and 10" with the capacities of 90, 120, 150 cubic meters per hour and 160, 210, 280 cubic meters per hour respectively. The capacity values will be the subject of further research and updating to enable the filling in the whole range of necessary capacities of borehole pumps with minimal reduction efficiency (up to 3%) on the borders of the range.
Review the parametres of submersible borehole pump’s stages for water supply
Keywords: диверсифікація джерел водопостачання; типорозмірний ряд; ККД; осьові ступені; water supply; standard series; efficiency; axial stage